Methods in Metallomics, Proteomics, and Toxicology: Development and Applications of Laser Ablation Inductively Coupled Plasma Mass Spectrometry and Native SDS-PAGE - (:unkn) unknown (My University, 2013)
Polyacrylamide gel electrophoresis (PAGE) is a bio-analytical method used to separate proteins in solution into an array of individual bands of proteins in a gel matrix. Current PAGE methods, however, have severe limitations in simultaneously maintaining a protein's native structure and association with transition metals while providing adequate resolution. Laser Ablation Inductively Coupled Plasma Mass Spectrometry (LA-ICP-MS) provides a means to perform trace to ultra-trace level inorganic analysis of solid samples such as dried PAGE gels containing metallo-protein arrays. Current LA-ICP-MS methods involving the analysis of PAGE gels, however, have been limited in their effective use by inadequate limits of detection to effectively detect trace level metallo-proteins on dried PAGE gels, and to date, have been mostly utilized as proof of principle experiments. The goal of this investigation was to develop a LA-ICP-MS method to provide adequate detection limits for trace level analysis of isolated metallo-protein bands on dried PAGE gels, and to develop a native PAGE method to adequately resolve protein bands from complex protein mixtures in solution. In addition, a LA-ICP-MS method was developed to detect trace level amounts of toxic metals in organisms to provide a means of performing "top-down" experiments involving toxic metal trafficking from organism exposure, to protein targets of toxic metals. Data are presented in support of the newly developed PAGE-LA-ICP-MS, Native Sodium Dodecyl Sulfate PAGE method (NSDS-PAGE), and toxic metal analysis of organisms, which together provide the means to separate and detect metallo-proteins from complex proteomic samples, and locate toxic metal binding sites in organisms. These findings and new methods provide, for the first time, the means to effectively study complex protein mixtures in the context of metallomics, and identify toxic metal binding sites in organisms.
Keywords: Inductively Coupled Plasma Mass Spectrometry; LA-ICP-MS; Laser Ablation; Metallomics; NSDS-PAGE; Proteomics